Typical Forensic Situations Arising When Considering Land Disputes - A. Yu. Butyrin; O. V. Zhukova; E. B. Stativa (Теория и практика судебной экспертизы)
The article presents a detailed examination of typical forensic situations requiring various specialized knowledge for their resolution, primarily in the field of land management. The first of them stems from land disputes over the location, configuration and area of land, as well as real estate related to it. The article presents a list of issues to be resolved by a forensic land surveyor who should have specialized knowledge in the fields of land management, cadastre and registration of real estate as well as from related fields. The second situation is due to the conflicts related to the right of shared ownership on land, dwellings and household constructions located at the premises. Forensic research of this type is presented in stages. It is noted that in this situation both specialized land management and engineering knowledge is applied, which allows to define the type and kind of buildings located on the land in question, the degree of their physical wear and tear, the size of premises as well as other technical characteristics which collectively enable an expert to say whether it is possible to actually split the disputed house and grounds, to consider its options and present them graphically. The third forensic situation is aimed at reviewing the question of whether the building under study is an obstacle to the use of the land (unauthorized construction). A judge’s and expert’s purview in resolving such issues is defined. Particular attention is paid to field observations including search, detection, fixation and evaluation of the characteristics of the construction site located on the land plot. The fourth situation involves disputes over the cadastral value of land plots engaging both a forensic expert and an appraiser. It is shown that although both determine the value of the disputed property their activity differs significantly.